MST1 controls murine neutrophil homeostasis via the G-CSFR/STAT3 axis - Masgrau-Alsina, Sergi; Wackerbarth, Lou Martha; Lim, Dae-sik; Sperandio, Markus (Frontiers in Immunology, 2022)
The release of neutrophils from the bone marrow into the blood circulation is essential for neutrophil homeostasis and the protection of the organism from invading microorganisms. Granulocyte colony-stimulating factor (G-CSF) plays a pivotal role in this process and guides granulopoiesis as well as the release of bone marrow neutrophils into the blood stream both during homeostasis and in case of infection through activation of the G-CSF receptor/signal transduction and activation of transcription 3 (STAT3) signaling pathway. Here, we investigated the role of the mammalian sterile 20-like kinase 1 (MST1) for neutrophil homeostasis and neutrophil mobilization. We found increased plasma levels of G-CSF in Mst1-/- mice compared to wild type mice both under homeostatic conditions as well as after stimulation with the proinflammatory cytokine TNF-α. In addition, G-CSF-induced mobilization of neutrophils from the bone marrow into the blood circulation in vivo was markedly reduced in the absence of MST1. Interestingly, this was not accompanied by differences in the number of blood neutrophils. Addressing the underlying molecular mechanism of MST1-regulated neutrophil mobilization, we found reduced STAT3 phosphorylation and impaired upregulation of CXCR2 in Mst1-/- bone marrow neutrophils compared to wild type cells, while JAK2 phosphorylation was not altered. Taken together, we identify MST1 as a critical modulator of neutrophil homeostasis and neutrophil mobilization from the bone marrow, which adds another important aspect to the complex role of MST1 in regulating innate immunity.